Social Media Marketing Activity and Cafe Atmosphere as Predictors of Revisit Intention at Northeast Coffee Padang - Kevin Oktrianda Muda; Youmil Abrian (Journal of Multidimensional Management, 2026)
This study examines whether social media marketing activity and cafe atmosphere predict consumers' revisit intention at Northeast Coffee Padang. A quantitative cross-sectional survey was conducted with 337 consumers selected through purposive sampling. Eligible respondents were at least 18 years old, had previously visited the cafe, had been exposed to Northeast Coffee's Instagram content, and were able to evaluate the cafe atmosphere. Data were collected using a five-point Likert-scale questionnaire and analyzed using multiple linear regression in SPSS 26. The overall model was significant (F = 33.823, p < 0.001) and explained 16.8% of the variance in revisit intention (adjusted R2 = 0.163). Social media marketing activity had a positive but modest effect (B = 0.094, beta = 0.120, p = 0.027), whereas cafe atmosphere was the stronger predictor (B = 0.243, beta = 0.348, p < 0.001). The findings indicate that Northeast Coffee should prioritize improvements to the physical cafe environment while strengthening the consistency, interaction, accessibility, and credibility of its Instagram communication. The relatively low R2 also indicates that revisit intention is substantially influenced by factors outside the present model.